2010
DOI: 10.1051/0004-6361/201014252
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of high-mass cluster forming clumps

Abstract: Aims. We have searched for star formation activity (mainly infall and outflow signatures) in a sample of high-mass molecular clumps (M > 100 M ) in different evolutionary stages and with a wide range of surface densities, with the aim of looking for evolutionary trends and testing observationally recent theoretical models which predict the need for a minimum surface density to form high-mass stars. Methods. Our sample has been selected from single-dish 1.2 mm continuum surveys and is composed of 48 massive mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
86
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 50 publications
17
86
2
Order By: Relevance
“…2). We have identified the lines detected with signal-to-noise ratio > ∼ 5, which correspond to typical main beam temperatures ∼0.1 K. Most of the lines detected toward all the sources of the sample correspond to simple molecules such as N 2 H + , C 2 H, NH 2 D, or H 13 CN, which are typically found tracing the dense gas in YSOs (e.g., Tafalla et al 2004;Padovani et al 2011;Busquet et al 2011;Fontani et al 2012), and molecules such as SiO and HCO + typically used to trace the outflow emission (e.g., Tafalla et al 2010;López-Sepulcre et al 2010;Codella et al 2013). For twelve of the fourteen sources, we also detected CH 3 CN emission, which is a tracer typically found in association with hot cores (e.g., Olmi et al 1993Olmi et al , 1996Sánchez-Monge et al 2010.…”
Section: Molecular Line Emissionmentioning
confidence: 96%
See 2 more Smart Citations
“…2). We have identified the lines detected with signal-to-noise ratio > ∼ 5, which correspond to typical main beam temperatures ∼0.1 K. Most of the lines detected toward all the sources of the sample correspond to simple molecules such as N 2 H + , C 2 H, NH 2 D, or H 13 CN, which are typically found tracing the dense gas in YSOs (e.g., Tafalla et al 2004;Padovani et al 2011;Busquet et al 2011;Fontani et al 2012), and molecules such as SiO and HCO + typically used to trace the outflow emission (e.g., Tafalla et al 2010;López-Sepulcre et al 2010;Codella et al 2013). For twelve of the fourteen sources, we also detected CH 3 CN emission, which is a tracer typically found in association with hot cores (e.g., Olmi et al 1993Olmi et al , 1996Sánchez-Monge et al 2010.…”
Section: Molecular Line Emissionmentioning
confidence: 96%
“…according to its emission or not at mid-IR wavelengths according to López-Sepulcre et al (2010). (d) Parameters obtained from the singletemperature, modified black body fit to the spectral energy distribution (see Sect.…”
Section: 1) (C) Sources Classified As Ir-luminous (Irl) or Ir-dark mentioning
confidence: 99%
See 1 more Smart Citation
“…1, Beltrán et al 2006), and found to be not blended with nearby millimeter clumps, which allows a clear identification of the fragments. Its high mass and column density make it a potential site for the formation of massive stars and rich clusters, according to observational findings (Kauffmann & Pillai 2010;Lopez-Sepulcre et al 2010). The clump was classified as an infrared dark cloud because it was undetected in the images of the Midcourse Space Experiment (MSX) infrared satellite, although more sensitive images of the Spitzer satellite revealed infrared emission at a wavelength of 24 µm (panel A in Fig.…”
Section: Introductionmentioning
confidence: 94%
“…Observationally, the infall motion is detected with a double-peaked, blue-skewed line profile, while complicated by density, molecular abundance, and excitation temperature. Nevertheless, clear global infall at clump scale is difficult to detect (López-Sepulcre et al 2010;Reiter et al 2011) since local star formation also creates infall and outflow signatures. Infall rates of star-forming clumps are observed to be small, about 10% of the free-fall velocity (Rolffs et al 2011;Tan et al 2014;Wyrowski et al 2016), supporting a quasi-static picture.…”
Section: Introductionmentioning
confidence: 99%